(untitled) (Experimental biology, 2021)
According to the European Food Safety Agency (EFSA) campylobacteriosis, salmonellosis and escherichiosis are major foodborne pathogens and, as a consequence, a serious public health problem. Due to the uncontrolled use of antibiotics as food additives, the poultry industry was one of the first faced the problem of spreading antibiotic resistance among bacterial pathogens. The emergence of multidrug-resistant infections and the ineffectiveness of antibiotics is one of the main problems of modern veterinary medicine. The gradual increase in the number of multidrug-resistant bacteria has led to an increase in research on the use of bacteriophages to combat bacterial infections. Phage therapy is a very promising direction, due to the high specificity of bacteriophages, their harmlessness and the ability to reproduce directly on the pathogen. Phage therapy is a very promising alternative approach, due to the high specificity of bacteriophages, their harmlessness and the ability to reproduce directly on the pathogen. In addition, bacteriophages are the most abundant organisms and their approximate number on Earth can reach 1031, which is more than 10 times the number of described species of bacteria and is an almost inexhaustible source for isolating new, more effective strains. In this study, the distribution of E. coli strains on poultry farms in the Almaty region were analyzed, as well as studied the morphology of the CEC_KAZ_2018 bacteriophage and its lytic properties in relation to newly isolated E. coli strains. From samples of internal organs of chickens with signs of colibacillosis, 15 cultures of Escherichia coli were isolated and identified. Analysis of the phylogenetic groups of isolates showed that the majority (73.4%) belonged to phylogroup D. It was revealed that up to 50% of the isolates showed resistance to antibiotics of the third generation: ceftazidime, aztreonam, and ceftazidime / clavulanate. Findings of the current study on the spectrum of lytic activity showed that the bacteriophage CEC_KAZ_2018 is able to lyse 10 out of 15 isolated cultures. Thus, this bacteriophage is a very promising candidate for the creation of antibacterial agents to combat colibacillosis in chickens.